2017
DOI: 10.1111/jcpp.12803
|View full text |Cite
|
Sign up to set email alerts
|

Language and reading comprehension in middle childhood predicts emotional and behaviour difficulties in adolescence for those with permanent childhood hearing loss

Abstract: BackgroundPermanent childhood hearing loss (PCHL) is associated with an elevated level of emotional and behaviour difficulties (EBD). In children and adolescents with PCHL, EBD has been found to be linked to language ability in children with PCHL. The present study was designed to test whether childhood language and/or reading comprehension abilities of children with PCHL predict subsequent EBD in adolescence.MethodsLanguage comprehension (LC) and reading comprehension (RC) were measured at ages 6–10 years (Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…The auditory system involves a series of complex distributed cerebral networks and its impairment affects psychosocial, emotional and cognitive development (Stevenson et al, 2018). Hearing-impaired children are at increased risk for learning disabilities (S. M. R. Choi, Kei, & Wilson, 2020) and even within the normal range, better hearing has been associated with better reading skills, working memory and nonverbal IQ in a sample of 1,638 UK school children (Moore, Zobay, & Ferguson, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The auditory system involves a series of complex distributed cerebral networks and its impairment affects psychosocial, emotional and cognitive development (Stevenson et al, 2018). Hearing-impaired children are at increased risk for learning disabilities (S. M. R. Choi, Kei, & Wilson, 2020) and even within the normal range, better hearing has been associated with better reading skills, working memory and nonverbal IQ in a sample of 1,638 UK school children (Moore, Zobay, & Ferguson, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A recent psychometric evaluation of the HUI3 and PedsQL TM Version 4.0 Generic Core Scales in Australian pre-school children with low language or congenital hearing loss found that the PedsQL TM may not be as sensitive as the HUI3 in distinguishing HRQoL impairments in children with and without low language [37]. It is likely that the hearing and speech attributes of the HUI3 allow it to be particularly sensitive at detecting the specific effects of hearing and language losses on the daily lives of children and adolescents, while the PedsQL may be more sensitive to social aspects of HRQoL that are particularly salient in these adolescents [22][23][24]. The HUI3 and PedsQL TM Version 4.0 Generic Core Scales are each underpinned by distinct conceptual models with distinct attribute sets and scoring algorithms and as such should be viewed as complementary tools for assessing the HRQoL of children or adolescents with PCHL.…”
Section: Discussionmentioning
confidence: 99%
“…The normally hearing comparison group had been identified using an algorithm developed by the investigators based on the dates of birth of the required number of children with normal hearing within each district and for each screening period. Further assessment of the sample was undertaken in the Hearing Outcomes at Teen Age project at a mean age of 16.9 (SD: 1.4) years [18][19][20][21][22][23][24].…”
Section: Study Background and Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Eigsti and colleagues 24 demonstrated, in a sample of internationally adopted children aged 4–13 years, that top-down cognitive assessments including measures of explicit memory and cognitive control differed between children who experienced early IC and matched children from biological families, yet differences between the groups in bottom-up implicit learning processes were unremarkable. Thus, although the results are complex, they have important implications for our understanding of the unique needs of this population given the critical role of language as a higher-order ability that underlies communication, learning, and self-regulation, and its strong predictive power with respect to outcomes in a variety of domains for typically developing and vulnerable populations 25 28 .…”
Section: Introductionmentioning
confidence: 99%